Building Trust for Resilience Development Among High School Seniors - Subedi, Tika Prasad (Brixton Scholarly Review, 2025)
This study investigates the critical role of trust in fostering educational resilience and enhancing learning outcomes by creating supportive, psychologically safe environments for both students and teachers. Utilizing a narrative research method under qualitative design, data was gathered through surveys and open interviews with students in diverse educational settings. The study analyzed the impact of open communication, empathy, and positive reinforcement on building trust and promoting resilience. The results demonstrate that trust, rooted in consistent teacher-student interactions, significantly enhances students' ability to engage with challenges. For example, open communication encourages students to share their struggles and achievements, while empathy from teachers creates an atmosphere of acceptance and validation. Specific evidence highlighted those students who experienced positive reinforcement felt more motivated and resilient in their academic endeavors, further deepening their trust in their educators. The study concludes that trust is a foundational element in educational environments, crucial for building student resilience and promoting academic success. Educators and institutions should prioritize transparent communication, empathy, and consistent encouragement to create a culture of trust, which in turn supports student growth and long-term achievement.